2004
DOI: 10.1007/s10067-004-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying pain threshold and quality of life of fibromyalgia patients

Abstract: The most typical symptom of fibromyalgia (FM) is diffuse pain, and pain at specific points-tender points-is crucial for its diagnosis. By comparing healthy individuals and FM patients, this study was aimed at assessing pain and quality of life of Brazilian females with FM, while seeking for a correlation between pain threshold and quality of life. A total of 178 women were evaluated: 124 were FM patients and 54 were healthy women. Pain threshold at tender points was quantified by dolorimetry, and diffuse pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 30 publications
7
37
0
8
Order By: Relevance
“…Widespread and chronic pain, which is the major symptom of FM, can become so intense that it may severely affect one's work life, daily activities, and quality of life (22,23). FIQ is a questionnaire form used to evaluate quality of life, functional capacity, work status, psychological disorders, and physical symptoms in FM patients (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread and chronic pain, which is the major symptom of FM, can become so intense that it may severely affect one's work life, daily activities, and quality of life (22,23). FIQ is a questionnaire form used to evaluate quality of life, functional capacity, work status, psychological disorders, and physical symptoms in FM patients (23).…”
Section: Discussionmentioning
confidence: 99%
“…FIQ is a questionnaire form used to evaluate quality of life, functional capacity, work status, psychological disorders, and physical symptoms in FM patients (23). In a quality of life study comparing patients with RA and FM, and controls using FIQ and SF-36, it was found that RA and FM patients had a poorer quality of life compared to controls, and mental health was found to be worse in FM patients compared to RA patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…FMS, which is a chronic rheumatismal disease does not cause injury or deformations to the joints, but by leading to significant difficulties in functional capacity and the undertaking of daily activities, family relationships and social performance are negatively affected [52]. The main symptom of FMS is widespread and chronic pain [53]. This pain in FMS has a negative effect on the patient's quality of life and functional capacity.…”
Section: Fibromyalgia and Quality Of Lifementioning
confidence: 99%
“…Several studies have reported that the FIQ scores of quality of life in FMS patients have been found to be significantly low compared to the control group [52][53][54]. In a study by Sivas et al, of life was found to be lower in the FMS group [55].…”
Section: Fibromyalgia and Quality Of Lifementioning
confidence: 99%
“…Pain threshold of trigger points of most tender were reported by participants upon digital pressure stimulation by a trained single examiner, marked with demographic pencil and considered positive when values were lower than 2.6 kg/cm 2 according to Marques et al 22 . Pain threshold reflects the lowest intensity of pressure at which an individual perceives pain 22 . Severity of symptoms: teeth clenching, sleeping difficulty and primary tension type headache were assessed using Visual Analogical Scales (VAS) at the time of the assessment.…”
Section: Painmentioning
confidence: 99%